Color change and physicochemical properties of bleached enamel with hydrogen peroxide, violet light or ozone - Tavares, Nayara Rodrigues Nascimento Oliveira (2019)
The aim of this study was to assess the bleaching effect and physicochemical on enamel of a violet light and ozone, associate or not to hydrogen peroxide, compared to 35% hydrogen peroxide. Enameldentin blocks from human molars were randomly allocated to receive one of following bleaching protocols (n=15): 35% hydrogen peroxide, violet light, ozone, the association between hydrogen peroxide with ozone or violet light. All protocols were performed in two sessions with a 48h interval between them. Color (spectrophotometer) and mineral composition (Raman spectroscopy) of tooth were measured before and after the bleaching procedures. Color changes were calculated by ΔEab and ΔE00, and whitening index was calculated in both assessment times. Surface roughness of bleached specimens was measured by atomic force microscope. Data were analyzed by One-way ANOVA or two-way repeated measure ANOVA followed by Tukey’s test (α = 0.05). Lowest values of color changes (either measured by WI, ΔEab or ΔE00) were observed for violet light and ozone used in absence of hydrogen peroxide. Violet light associate to hydrogen peroxide was unable to improve the color changes observed for the peroxide alone but combining ozone and hydrogen peroxide yield the highest color changes. Irrespective of bleaching protocol, the bleached enamel presented higher contents of PO4 and CO3-2 than those observed at baseline. No significant difference was observed between the tested bleaching protocols regarding the surface roughness of bleached enamel. It is possible to conclude that either violet light or ozone had reduced effects on the enamel color change when used alone. Ozone therapy improved the bleaching effect of 35% hydrogen peroxide. All evaluated protocols resulted in similar modification on enamel surface.